Supplementary Table S2 from Phase II Trial of Pembrolizumab and Anti-CD3 x Anti-HER2 Bispecific Antibody-Armed Activated T Cells in Metastatic Castration-Resistant Prostate Cancer - Ulka N. Vaishampayan (15051039) (2025)
Shows Phenotype, Viability, and Cytotoxicity of the Product.